The good samaritan strikes again [large type] - McManus, Patrick F. (G.K. Hall large print book series, 1993)
A collection of humorous anecdotes by the author of The Night the Bear Ate Goombaw discusses worrying, McManus's first kiss, relieving stress through fantasies, and more.